(untitled) (Indonesian Art and Justice Review, 2024)
Community-based art projects have emerged as powerful tools for promoting social justice in Indonesia, offering marginalized communities opportunities to engage in creative expression, challenge social inequalities, and build collective identity. This paper examines the role of community art initiatives in fostering social justice, focusing on projects that address issues such as poverty, environmental degradation, and gender inequality. By looking at specific community art projects in urban and rural Indonesia, the paper analyzes how these projects facilitate dialogue, raise awareness, and empower individuals to advocate for their rights. Additionally, it discusses the challenges these initiatives face in navigating local politics, funding, and community expectations, as well as their potential to effect lasting social change.